Perceived Internal Respect and Level of Religiosity Towards Improving the Performance of Campalagian Community Health Center - Marjuni, Nurmaya; Muchlis, Nurmiati; Batara, Andi Surahman (Journal of Aafiyah Health Research (JAHR), 2023)
Background: Perceived Internal Respect and Level of Religiosity Towards Improving the Performance of Campalagian Community Health Center. Aim: Campalagian Health Center is one of the puskesmas that has the largest working area in Polewali Mandar Regency, but observations found perceived internal respect and the level of religiosity in employees are less described, thus affecting performance. The purpose of this study is to analyze the effect of perceived internal respect and the level of religiosity on improving employee performance. Method: Type of quantitative research with a cross sectional approach. The population of 46 permanent employees (ASN) at the Campalagian Health Center, Polewali Mandar Regency with sample selection using total sampling. Results: Respondents were dominated by health worlkers with female gender (89.1%), most of whom had vulnerable ages 36-45 years (60.9%) and D3 graduates (41.3%) also the most length of work was >10 years (65.2%); Perceived internal respect and level of religiosity have a significant effect on improving employee performance (sig value = 0.042<0.05); Based on the magnitude of the influence, a regression coefficient value of 0.144 was found where every increase in perceived internal respect by 1 unit will increase the value of employee performance by 0.144. Conclusion: The need to increase perceived internal respect at the Campalagian Puskesmas Polewali Mandar Regency through cared contribution where the puskesmas needs to appreciate all the contributions and achievements of its employees. Also related to the level of religiosity through ritualism where employees need to believe that one's commitment to religion will be rewarded with good things in life.